2020
DOI: 10.3390/insects11020128
|View full text |Cite
|
Sign up to set email alerts
|

The Mosquito Larvicidal Activity of Essential Oils from Cymbopogon and Eucalyptus Species in Vietnam

Abstract: The larvicidal activity of essential oils (EOs) extracted from Cymbopogon citratus, Cymbopogon winterianus, Eucalyptus citriodora, and Eucalyptus camaldulensis aromatic plants grown in Vietnam was evaluated on Aedes aegypti larvae. The EOs were hydro-distilled in a Clevenger-type apparatus. The EOs were analyzed by gas chromatography-mass spectrometry (GC-MS). The mortality rates obtained from the bioassays were used to calculate the lethal concentrations (LC 50 ) of the EOs by the probit analysis method. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 33 publications
2
26
2
1
Order By: Relevance
“…In a recent study, the essential oils of C. citratus was very effective against the larvae of Ae. aegypti in Vietnam at higher LC50 of 38.8mg/L, almost the same found in this study even though the study did not shows the screened phytochemicals presence in the anhydrous sodium sulfate extracts, as the presence of the phytochemicals depends on the extracting solvent [15] which could be responsible for the efficacy of the C. citratus extract against Aedes aegypti [26] . Several studies have reported the insecticidal activities of this plant extracts on insects such as Musca domestica and different mosquitoes and several other flying arthropods and found it effective on adulticides, repellent and inhibition of life cycle developmental stages [27] .…”
Section: Discussionsupporting
confidence: 77%
“…In a recent study, the essential oils of C. citratus was very effective against the larvae of Ae. aegypti in Vietnam at higher LC50 of 38.8mg/L, almost the same found in this study even though the study did not shows the screened phytochemicals presence in the anhydrous sodium sulfate extracts, as the presence of the phytochemicals depends on the extracting solvent [15] which could be responsible for the efficacy of the C. citratus extract against Aedes aegypti [26] . Several studies have reported the insecticidal activities of this plant extracts on insects such as Musca domestica and different mosquitoes and several other flying arthropods and found it effective on adulticides, repellent and inhibition of life cycle developmental stages [27] .…”
Section: Discussionsupporting
confidence: 77%
“…In folk medicine, it is used for the treatment of anxiety, as a sedative, and for pain disorders [ 92 ]. Some studies demonstrated that the plant has anticonvulsant effects [ 93 ], anti-larvicidal effects against Aedes aegypti [ 94 ], and antibacterial and antifungal effects, including anti- Candida action [ 95 ]. The essential oils extracted from C. nardus L. and C. winterianus Jowitt species showed, in different studies, to be highly effective in combating C. albicans oral biofilms.…”
Section: Plant Extracts Against Oral Biofilm Formed By Candida Sppmentioning
confidence: 99%
“…Furthermore, multiple reports suggest LEO can suppress larval growth and production in various insects [160][161][162][163][164]. Lemongrass active constituent citral in combination with other components can regulate neuroreceptor activities, signal transduction, hormonal balance, membrane integrity, and cytotoxicity in insects [165,166]. Other minor components including caryophyllene, caryophyllene oxide, and germacrene-D discourage insect invasion and are effective against common houseflies and mosquitoes as well [167].…”
Section: Miscellaneousmentioning
confidence: 99%